(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The issue of sustainable development is an interesting international issue because it is related to the development process implemented in various countries in the world. The concept of sustainable development emerged in response to the negative impacts of conventional development that tend to ignore environmental, social, and economic sustainability. The issue of sustainable development came to the fore for the first time since the Stockholm Conference organized by the United Nations (UN) in 1972 as the first attempt to discuss global environmental issues and sustainable development. This paper aims to conduct a digital analysis of sustainable development issues. This research tends to be qualitative because it uses text data that appears on many digital social media and then analyzes these data so that certain image / graphic patterns and certain numbers are easier to understand in general. The analysis was conducted using the social media monitor platform Brand24. The results of digital analysis show interesting trends in sustainable development issues in terms of volume of mentions, sentiment analysis, social media reach, non-social media reach, the context of discussion, public profiles, influential sites, and trending hashtags.